Malay-Nusantara Islamic Civilization: A Historical Comparison of the Roles of the Demak Sultanate and Brunei Darussalam - Yasa, I Komang Kartika; Purnomo, Antonius Dewanto (Proceedings: International Seminar On Educational Studies, 2025)
This study examines the comparative roles of the Sultanate of Demak and the Sultanate of Brunei Darussalam in shaping Islamic civilization within the Malay–Nusantara region. The research is grounded in the need to understand Southeast Asian Islamic civilization as a product of religious propagation, maritime trade, and political interaction. The objective is to explain how both sultanates integrated religion and political authority to form distinctive Islamic governance rooted in local culture. Employing a historical–comparative method, the study analyzes primary sources such as classical manuscripts and chronicles, along with relevant secondary literature. The findings reveal that the Sultanate of Demak represents a revolutionary and transformational model of Islamic civilization, emphasizing Islamization through cultural propagation and community-based education. Conversely, the Sultanate of Brunei reflects an evolutionary and continuous model, institutionalizing Islamic values through the Melayu Islam Beraja (MIB) monarchy, which upholds stability, morality, and the continuity of Islamic law. The novelty of this research lies in its comparative analysis of two complementary maritime Islamic paradigms: Demak as a catalyst for social transformation and Brunei as a guardian of monarchical continuity. The implications suggest the importance of strengthening academic and historical collaboration among ASEAN countries to enhance understanding of maritime Islamic civilization as a foundation for intellectual and cultural integration in Southeast Asia.